High temperature exposure reduces the susceptibility of Helicoverpa armigera to its nucleopolyhedrovirus (HearNPV) by enhancing expression of heat shock proteins. Issue 6 (21st April 2022) - Shen, Zhong‐Jian; Liu, Yan‐Jun; Cheng, Jie; Li, Zhen; Michaud, J.P.; Liu, Xiao‐Xia
Abstract: BACKGROUND: High temperatures will occur more frequently with global warming, with potential impacts on the efficacy of biological control agents. Heat shock proteins (HSPs) are induced by high temperature, but their possible roles in pest resistance to entomopathogens remain unexplored. We investigated the effects of high temperature (35 °C) on Helicoverpa armigera resistance to H. armigera nucleopolyhedrovirus (HearNPV) and the putative roles of HSPs in this process. RESULTS: Even short periods (24 h) of high temperature (35 °C) reduced mortality in HearNPV‐infected H. armigera larvae. Sustained 35 °C exposure significantly shortened developmental time, and increased fresh weight and locomotor activity in infected larvae. Moreover, high temperature inhibited virus replication and thickened the epidermis of H. armigera, resulting in reduced spread of infection from cadavers. Real‐time polymerase chain reaction (PCR) analysis showed that expression of 11 HSP genes was altered by the 35 °C treatment, and that mostly small heat shock protein (sHSP) genes were up‐regulated, the same sHSPs were induced when larvae were infected with HearNPV. Finally, RNA interference (RNAi) suppression of these sHSPs showed that only Hsp24.91 and Hsp21.8 diminished H. armigera defensive responses to HearNPV infection. CONCLUSION: Even short periods of exposure to high temperature can significantly reduce susceptibility of H. armigera larvae to HearNPV by stimulating the production of sHSPs which enhance immune responses, with important implications for the use of entomopathogens as biological control agents under global warming scenarios. © 2022 Society of Chemical Industry. Abstract : Even short periods of exposure to high temperature can significantly reduce susceptibility of Helicoverpa armigera larvae to H. armigera nucleopolyhedrovirus (HearNPV) by stimulating the production of small heat shock proteins (sHSPs) which enhance immune responses. These findings remind us to pay attention to the impact of global warming on pest control.